Risk of Soil-Transmitted Helminthiasis among Agrarian Communities of Kogi State, Nigeria - Joy T. Anunobi (Ubiquity Press, 2019)
Background: Soil-transmitted helminths (STH) have remained a major threat to humans, especially children in developing countries, including Nigeria. Interventions have always been geared towards school-aged children, neglecting preschool-aged children and occupational risk adults. The Soil-Transmitted Helminthiasis Advisory Committee (STHAC) recently suggested incorporating other at-risk groups. Objective: This study assessed the associated risk of STH infection among agrarian communities of Kogi State, Nigeria. Methods: A total of 310 individuals of all ages participated in the cross-sectional survey. Stool samples were analyzed using standard Kato-Katz method. Results: A total of 106 (34.2%) individuals were infected with at least one STH. Hookworm was the most prevalent (18.1%); followed by 'Ascaris lumbricoides' (16.8%). Worm intensity was generally light. Prevalence of infection was similar between four age groups considered (preschool, school, ‘women of reproductive age’ and older at-risk group). Poor socio-economic status (SES) was a major risk for STH infection. Using a 20-asset based criteria, 68 (23.1%) and 73 (24.7%) of 295 questionnaire respondents were classified into first (poorest) and fifth (richest) wealth quintiles respectively. Risk of infection with STH was 60% significantly lower in the richest wealth quintile compared to the poorest (Prevalence Ratio [PR] = 0.4843, 95% CI = 0.2704–0.8678, p = 0.015). Open defecators were more likely to harbour STH than those who did not (PR = 1.7878, 95% CI = 1.236–2.5846, p = 0.00201). Pit latrine and water closet toilets each approximately reduced STH infection by 50% (p < 0.05). Conclusion: Preventive chemotherapy for all age groups, health education and provision of basic amenities especially toilets are needed in order to achieve the goal toward the 2020 target of STH control.